The effects of on-call duties on cognitive functions in anaesthesia residents HUSM - Balsam Mahdi Nasir, Al Zurfi (2010)
Selected anthropometric parameters in relation to glycaemic control and associated factors in Malay diabetic type 2 patients in HUSM Simple anthropometric measurements have been used as surrogate measurement of obesity. There are many techniques that can measure body compositions for overweight and obesity however costs limit their use. The increased in obesity and diabetes type 2 epidemics worldwide with adoption of the new term "diabesity" lead to an increase in the concern about obesity measurements in diabetic patients. The objectives of the study were to examine the relationship between selected anthropometric measurements namely BMI, we and WHtR with glycaemic control among Malay type 2 diabetics in Hospital Universiti Sains Malaysia, Kelantan, Malaysia. A cross sectional study was conducted involving one hundred and ninety Malay type 2 DM patients attending diabetic clinic in Hospital Universiti Sains Malaysia between 7th and 281h February 2010. Information on socio demographic profile, medical history, drug history, smoking, physical activity and dietary fiber intake habit of the respondents were taken. Physical and anthropometric measurements which included BMI, we, WHtR, BF% and BP were taken. Medical records were reviewed for biochemical measurements including HbA1c, fasting blood glucose and lipid profile. All the one hundred and ninety respondents were Malay and confirmed type 2 diabetes mellitus. Female were slightly more (55.3%) than males (44.7%). The mean difference between male and female in all numerical variables was not significant except for age (years), income/month (RM), HDL (mmol/L), we (em) and BF% (p Value< 0.05). The association between gender and type of occupation, type of education, family history of diabetes and smoking were significant (p value < 0.05). Using WHO and WPR definitions to compare the proportion difference of obesity classes using BMI were: In both genders the percentage of normal and overweight is lower according to WPR compared to WHO classification while the percentage is higher for obese. Using We the proportion of central obesity tends to be higher in both genders according to WPR classifications. The correlations between selected anthropometric parameters (BMI, We and WHtR) with glycaemic control were not significant (p value > 0.05), weak and negative. we was the only anthropometric parameter that significantly associated with uncontrolled HbAtc (OR = 0.13, 95% ei=0.03, 0.57) after adjustment for age (years), LDL (mmoi/L), fiber diet, physical activity and type ofDM drugs. Anthropometric parameters measured in this study were not significantly associated to glycaemic control in diabetic patients after adjustment for other potential variables. The strength of association between BMI, we and WHtR was incomparable due to insignificant and weak association with glycaemic control.